A collaborative endeavour to integrate leadership and person-centred ethics: a focus group study on experiences from developing and realising an educational programme to support the transition towards person-centred care - Qarin Lood; Eric Carlström; Charlotte Klinga; Emmelie Barenfeld (BMC, 2024)
Abstract Background Ensuring the transition towards person-centred care is a growing focus in health and social care systems globally. Presented as an ethical framework for health and social care professionals, such a transition requires strong leadership and organisational changes. However, there is limited guidance available on how to assist health and social care leaders in promoting person-centred practices. In response to this, the Swedish Association of Health Professionals and the University of Gothenburg Centre for Person-Centred Care collaborated to develop an educational programme on person-centred leadership targeting health and social care leaders to support the transition towards person-centred care in Sweden. The aim with this study was to explore programme management members' experiences from the development and realisation of the programme. Methods Focus group discussions were conducted, involving 12 members of the programme management team. Data from the discussions were analysed using a structured approach with emphasis the collaborative generation of knowledge through participant interaction. Results The analysis visualises the preparations and actions involved in programme development and realisation as a collaborative endeavour, aimed at integrating leadership and person-centred ethics in a joint learning process. Participants described the programme as an ongoing exploration, extending beyond its formal duration. Leadership was thoughtfully interwoven with person-centred ethics throughout the programme, encompassing both the pedagogical approach and programme curriculum, to provide leaders with tangible tools for their daily use. Conclusions According to our analysis, we conclude that a person-centred approach to both development and realisation of educational initiatives to support person-centred leadership is essential for programme enhancement and daily implementation of person-centred leadership. Our main message is that educational initiatives on the application of person-centred ethics is an ongoing and collaborative process, characterised by an exchange of ideas and collective efforts.